A self-healing key distribution scheme based on vector space secret sharing and one way hash chains - Tian, Biming; Han, Song; Dillon, Tharam S.; Das, S. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
An efficient self-healing key distribution scheme with revocation capability is proposed for secure group communication in wireless networks. The scheme bases on vector space secret sharing and one way hash function techniques. Vector space secret sharing helps to realize general monotone decreasing structures for the family of subsets of users that can be revoked instead of a threshold one. One way hash chains contribute to reduce communication overhead. Furthermore, the most prominent characteristic of our scheme is resisting collusion between the new joined users and the revoked users, which is fatal weakness of hash function based self-healing key distribution schemes.